The effect of early versus late enteral feeding on the hypermetabolic response of the paediatric burned patient - Venter, Marcha (Department of Paediatrics and Child Health, 2017)
Background: Red Cross Children's Hospital treats an average of 2 000 children per annum with thermal injuries. Five hundred of these are new injuries and 60 patients have a total body surface area burn (TBSAB) that exceeds 20%. There is substantial evidence in adult burn literature that suggests that early enteral feeding (EEF) compared to initial starvation has a profound impact on the hormonal response, metabolic rate and gastrointestinal maintenance post thermal injury. However, research addressing these issues in the burned child (birth to 13 years old), are limited. Aim: To compare EEF, to delayed or late enteral feeding (LEF), and to evaluate whether the practice is beneficial in paediatric burned patients. Criteria: The criteria for the patients were (a) a burn less than 24 hours old and a TBSAB more than or equal to 20%, (b) an age of less than 13 years and (c) admission to the Red Cross Children's Hospital Burns Unit. Objectives: The objectives were to compare the effect of EEF and LEF on (1) the concentrations of insulin, insulin-like growth factor-1 (IGF1), glucagon, cortisol and growth hormone (GH), (2) the estimated energy expenditure (EEE) and calculated energy expenditure, (3) the respiratory quotient (RQ), (4) the intestinal permeability and (5) the clinical outcome. Methods: The children were assigned to either the EEF or LEF group. Nine patients in each study group completed the study successfully, with similar median ages (4.5 yr.), body weights (14 kg) and TBSAB (30%). The EEF group was enterally fed via a nasojejunal feeding tube within a median time of 10.75 hours post burn, whereas the LEF group fasted for a median of 54 hours, after which enteral feeds were introduced. This study is unique in that enteral feeds were used as part of the resuscitation regime in the EEF group. The EEF group received their full resuscitation volumes from the enteral feed at a median time of 16 hours from initiation. Venous blood samples were taken daily between 7h00 and 8h00, before breakfast, for the hormone measurements. The REE and RQ were measured by indirect calorimetry and compared to the recommended dietary allowances (RDA), Galveston and Solomon's equations, which estimate energy requirements. Small bowel permeability was measured by the sugar-absorption-test (SAT), and expressed as lactulose:rhamnose ratios.